144k views
4 votes
Use the quadratic formula to solve the equation 2x^2+2x-4=0

User Frogmanx
by
6.1k points

1 Answer

6 votes

Answer:

x = -2 or x = 1

Explanation:

The quadratic formula for the quadratic equation ax² + bx + c = 0:


x=(-b\pm√(b^2-4ac))/(2a)


2x^2+2x-4=0\qquad\text{divide both sides by 2}\\\\x^2+x-2=0


a=1,\ b=1,\ c=-2

Substitute:


x=(-1\pm√(1^2-4(1)(-2)))/(2(1))=(-1\pm√(9))/(2)=(-1\pm3)/(2)\\\\x_1=(-1-3)/(2)=(-4)/(2)=-2\\\\x_2=(-1+3)/(2)=(2)/(2)=1

User Jeanell
by
6.2k points